Amphiphilic Janus Particles Generated via a Combination of Diffusion‐Induced Phase Separation and Magnetically Driven Dewetting and Their Synergistic Self‐Assembly. Issue 16 (29th February 2016) - Wang, Xiuyu; Feng, Xueyan; Ma, Guiping; Yao, Li; Ge, Maofa
Abstract : Amphiphilic Janus particles are successfully obtained via a powerful strategy combining diffusion‐induced phase separation and magnetically driven dewetting. A large‐area, amphiphilic monolayer is been formed via a self‐assembly paradigm based on a synergy between the amphiphilicity, shape anisotropy, and external magnetic field. This functionality holds great promise for practical applications in intelligent coatings, anti‐bioadhesion, and antifouling surfaces.